ZDA in omejevanje reproduktivne avtonomije žensk - Burcar, Lilijana (Družboslovne razprave, 2024)
Liberal feminist movements primarily focus on women’s right to abortion, while neglecting restrictions and structural barriers that prevent women from accessing contraception in systems that do not offer (full) health insurance coverage. Based on systemic analysis and a historical-materialist approach, the article sheds light on different stages of limiting access to contraception for working poor and impoverished women in the USA as embedded in ACA and Title X programmes. Denying or restricting working poor and impoverished women’s access to full or at least subsidised contraception coverage leads to class differentiation among women in their ability to exercise their right to family planning and reproductive autonomy. In the wake of Dobbs, this holds new sinister implications and consequences for low-income and poor women’s right to reproductive freedom.
Keywords: človekove pravice; kontracepcija; pravice žensk; razredna diferenciacija; reproduktivna avtonomija; ZDA; ženske